Simulational Investigation of a High-Efficiency X-Band Magnetically Insulated Line Oscillator*supported by National Natural Science Foundation of China (No. 11075210) and the Special Financial Grant from the China Postdoctoral Science Foundation (No. 201104761). (October 2015) - Wang, Xiaoyu; Fan, Yuwei
Abstract The magnetically insulated line oscillator (MILO) is a gigawatt-class, coaxial crossed-field microwave tube, which is at present a major hotspot in the field of high-power microwaves (HPM) research. In order to improve the power conversion efficiency and eliminate or at least minimize anode plasma formation in the load region and radio frequency (RF) breakdown in the slow wave structure (SWS) section, an X-band MILO is presented and investigated numerically with KARAT code. The design idea is briefly presented and the simulation results are given and discussed. In the simulation, HPM is generated with peak power of 3.4 GW, maximum electric field of about 1 MV/cm, and peak power conversion efficiency of 14.0%, when the voltage is 559.1 kV and the current is 43.2 kA. The microwave frequency is pure and falls in the X-band of 9.0 GHz. The theoretical investigation and the simulation results are given to prove that the anode plasma formation and the RF breakdown can be effectively avoided or at least minimized, respectively.